Biallelic mutations in the homeodomain of NKX6-2 underlie a severe hypomyelinating leukodystrophy - Dorboz, Imen; Aiello, Chiara; Simons, Cas; Stone, Robert Thompson; Niceta, Marcello; Elmaleh, Monique; Abuawad, Mohammad; Doummar, Diane; Bruselles, Alessandro; Wolf, Nicole I; Travaglini, Lorena; Boespflug-Tanguy, Odile; et al. (Brain (London, England : 1878), 2017)
Hypomyelinating leukodystrophies are genetically heterogeneous disorders with overlapping clinical and neuroimaging features reflecting variable abnormalities in myelin formation. We report on the identification of biallelic inactivating mutations in NKX6-2, a gene encoding a transcription factor regulating multiple developmental processes with a main role in oligodendrocyte differentiation and regulation of myelin-specific gene expression, as the cause underlying a previously unrecognized severe variant of hypomyelinating leukodystrophy. Five affected subjects (three unrelated families) were documented to share biallelic inactivating mutations affecting the NKX6-2 homeobox domain. A trio-based whole exome sequencing analysis in the first family detected a homozygous frameshift change [c.606delinsTA; p.(Lys202Asnfs*?)]. In the second family, homozygosity mapping coupled to whole exome sequencing identified a homozygous nucleotide substitution (c.565G>T) introducing a premature stop codon (p.Glu189*). In the third family, whole exome sequencing established compound heterozygosity for a non-conservative missense change affecting a key residue participating in DNA binding (c.599G>A; p.Arg200Gln) and a nonsense substitution (c.589C>T; p.Gln197*), in both affected siblings. The clinical presentation was homogeneous, with four subjects having severe motor delays, nystagmus and absent head control, and one individual showing gross motor delay at the age of 6 months. All exhibited neuroimaging that was consistent with hypomyelination. These findings define a novel, severe form of leukodystrophy caused by impaired NKX6-2 function.